Health-Related Quality of Life and Associated Factors among Women on Antiretroviral Therapy in Health Facilities of Jimma Town, Southwest Ethiopia - Yetnayet Abebe Weldsilase; Melaku Haile Likka; Tolossa Wakayo; Mulusew Gerbaba (Advances in Public Health)
Background. This study examined health-related quality of life and associated factors among HIV positive women receiving antiretroviral therapy in health facilities of Jimma town. Methods. A cross-sectional study was conducted, and consecutive sampling technique was employed to select 377 HIV positive women who were on antiretroviral therapy. Quality of life was measured using WHOQOL-BREF tool. Descriptive statistics, bivariate, and multivariable logistic regression analyses were performed. P values < 0.05 and adjusted odds ratio with 95% of confidence interval were used to determine statistical significance and report associations between the quality of life and independent variables. Results. Among the sampled participants, 344 were interviewed, yielding 91% of response rate. The mean ± standard deviation age of the respondents was 34.07 ± 8.76 years and 80.5% of them were urban dwellers. The proportion of women reporting good health-related quality of life was found to be 46.5%. Specific to each domain, the mean ± standard deviation of level of independence domain was the highest (14.08 ± 3.07) followed by physical (13.46 ± 2.95), social relationships (13.27 ± 3.91), psychological (12.97 ± 2.47), environmental (12.94 ± 3.25), and spiritual (12.39 ± 2.84) domains. Good social support (AOR: 4.99; 95% CI: [2.88, 8.34]), higher wealth status (AOR: 1.85; 95% CI: [1.02, 3.39]), and being on antiretroviral therapy for shorter duration (AOR: 1.85; 95% CI [1.14, 3.03]) were independently associated with better overall health-related quality of life among the participants. Conclusions. The study demonstrated high proportion of HIV positive women on ART had poor health-related quality of life which was affected by wealth index, social support, and duration on antiretroviral therapy.